Inter-organizational relationships : management of inter-organizational relationships between the company and relationships and its partners : monographie - Fedotova, Irina; Krіvoruchko, Oksana; Bocharova, Nadezhda (Sienciea Scripts, 2022)
This monograph examines the theoretical foundations and practical approaches to managing inter-organizational relations between a company and its external partners. It highlights the strategic importance of cooperation, trust-building, and mutual value creation in a networked business environment. The study analyzes models of partnership governance, coordination mechanisms, and tools for enhancing collaboration effectiveness. Special attention is given to long-term relationship management, integration of digital technologies, and risk mitigation strategies. The findings offer insights into how companies can strengthen their competitive position through effective partner relationship management.
Keywords: inter-organizational relations; partner management; business networks; strategic partnerships; collaboration; governance models; trust; coordination; competitive advantage; digital integration